Public Service Policy in the Era of Fiscal Efficiency: A Case Study of Bandung City (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The study aims to analyze public service policy in the digital era in the City of Bandung. The research employs a qualitative case study method with descriptive analytical techniques. The findings indicate that public service policy in Bandung’s digital era remains suboptimal, as it is still predominantly top-down and administrative, with a primary focus on fiscal efficiency. As a result, quality, service equity, and public participation receive insufficient attention. Policy evaluation emphasizes administrative achievement rather than tangible societal impact, while the involvement of non-governmental actors and community participation remains limited, potentially reducing access to public services and overall community welfare. Digital service transformation is supported by local leadership, technological innovation, and multi-stakeholder partnerships; however, its effectiveness is hindered by budget rigidity, limited human resource capacity, fragmentation, and low digital literacy. Therefore, the study highlights the need for outcome-based, inclusive, and participatory policy reforms through service digitalization, strategic partnerships, budget refocusing, and strengthened outcome-oriented monitoring and evaluation, enabling public services to become more efficient, responsive, and sustainable.